Improving Students' Speaking Competence Through Simulation in SMA Al Islam 1 Surakarta Academic Year 2009/2010 - Wijayani A.N.R , Arifah (2012)
This research aims at observing the implementation of simulation teaching technique to the teaching of English Speaking at SMA Al Islam 1 Surakarta and its affect upon students' learning. The research was conducted at the first grade students of SMA Al Islam 1 Surakarta 2008/ 2009 academic year. In this research, the problem refers to the first grade students in learning English especially their speaking competence which is still low. The writer proposed simulation technique to solve students' problems. The research was a classroom action research. The research method included setting and time of the research, the subject of the research, the method of the research, the procedure of the research and technique of collecting data. The writer divided the action into three cycles and carried out in four steps namely action plan, action implementation, observation, and reflection. The cycles were determined at the time of implementation in which after looking at the result of the first cycle, then followed by the next cycles to see the consistency of the significant data. Based on the result, the writer drew a conclusion that the use of simulation technique really improved the students' achievement in learning English especially in speaking English. The improvement was quite significant which was reflected from the progress of students' score from one cycle to another. It also can be seen from their increasing motivation and interest.